Enhancing Vocational Education for Agribusiness Competence in the Era of Industry 4.0: A Study on Improving Curriculum Relevance and Graduate Readiness in Agricultural Product Processing - Kurniati Sari, Nove; Banyuriatiga, Banyuriatiga; Al-Hafiz , Ahmad Hasan; Zulkarnain, Riski (Mataram University, 2025)
The technological era of disruption 4.0, education plays an important role in preparing superior, skilled, professional, and competitive human resources. The Indonesian government must make comprehensive preparations, including improving quality education services that can produce graduates according to their fields of expertise. Vocational High School (SMK) focuses on developing students' ability to work in a particular field, adapt to the work environment, and see future job opportunities. In particular, the agribusiness expertise program for agricultural product processing in SMK has great potential to support the local economy and farmers' welfare. Evaluating the competency profile of SMK graduates in this field is crucial to ensure the curriculum's suitability with the job market's needs. This study aims to evaluate the profile of agribusiness competence in SMK, using data from the education curriculum, stakeholder perspectives, and the development of the agribusiness industry. The research method used is qualitative-quantitative, with data obtained through observation, interviews, and surveys at SMK Negeri 3 Tarakan, SMK Negeri 1 Nunukan, and several MSMEs in North Kalimantan. The results showed that several competence points had yet to be maximised in its application, such as quality management, food safety standards, and production process management. Factors that influence the suboptimal application of competencies include limited resources, facilities, and access to technology. This study recommends improving teaching staff qualifications, facilities and infrastructure, and access to technology to improve learning effectiveness. Thus, it is expected that vocational education in Indonesia can be more relevant and efficient in preparing graduates who are ready to face challenges and opportunities in the agribusiness sector of agricultural product processing.